Internal Grammar and Children's Grammatical Creativity against Poor Inputs - Belletti, Adriana (Frontiers in Psychology, 2017)
This article is about the unexpected linguistic behavior that young children sometimes display by producing structures that are only marginally present in the adult language in a constrained way, and that adults do not adopt in the same experimental conditions. It is argued here that children's capacity to overextend the use of given syntactic structures thereby resulting in a grammatical creative behavior is the sign of an internal grammatical pressure which manifests itself given appropriate discourse conditions and factors of grammatical complexity and which does not necessarily require a rich input to be put into work. This poverty of the stimulus type situation is illustrated here through the overextended use of a-Topics and reflexive-causative passives by young Italian speaking children when answering eliciting questions concerning the direct object of the clause.